Aspects of Social-Media Interaction and Society - Georgiana DRĂGHICI (POPESCU) (ACROSS)
Social media has managed to revolutionise the whole world, not just the concept of public relations. How often have we felt the need to capture a beautiful holiday moment – a snapshot to share on social media accounts? How often have we wanted to share our best culinary experiences with friends or followers? The examples could go on and on, and whether we realize it or not, we end up influencing our followers by what we choose to post online.